2022
DOI: 10.3389/fpsyt.2021.750798
|View full text |Cite
|
Sign up to set email alerts
|

Common and Specific Characteristics of Adolescent Bipolar Disorder Types I and II: A Combined Cortical Thickness and Structural Covariance Analysis

Abstract: BackgroundBy calculating cortical thickness (CT) and cortical structural covariance (SC), we aimed to investigate cortical morphology and cortical inter-regional correlation alterations in adolescent bipolar disorder type I (BD-I) and type II (BD-II) patients.MethodsT1-weighted images from 36 BD-I and 22 BD-II patients and 19 healthy controls (HCs) were processed to estimate CT. CT values of the whole brain were compared among three groups. Cortical regions showing CT differences in groups were regarded as see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Both BD I and BD II had reduced SC connections between superior frontal gyrus (SFG), postcentral gyrus (PCG), superior temporal gyrus (STG), and pars opercularis, while only type I patients had decreased SC connections between STG, inferior parietal gyrus (IPG), pars opercularis ( 20 ). In contrast to SCH, BD patients showed increased clustering coefficients in the left suborbital sulcus and the right superior frontal sulcus ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both BD I and BD II had reduced SC connections between superior frontal gyrus (SFG), postcentral gyrus (PCG), superior temporal gyrus (STG), and pars opercularis, while only type I patients had decreased SC connections between STG, inferior parietal gyrus (IPG), pars opercularis ( 20 ). In contrast to SCH, BD patients showed increased clustering coefficients in the left suborbital sulcus and the right superior frontal sulcus ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cortical thickness (CT) and surface area (SA) are important components that measure cortical morphometry. CT and SA abnormalities are commonly observed in neurodevelopmental disorders, including bipolar disorder ( 9 ), schizophrenia ( 10 ), autism ( 11 ), and attention-deficit/hyperactivity disorder ( 12 ). Shaw et al used 3D-T1WI's longitudinal study of the correlation between intelligence and cortical thickness in normal children and adolescents and found that in early childhood, there was a significant negative correlation between intelligence and cortical thickness, while with age, they gradually showed a positive correlation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%